PERAN KEPEMIMPINAN KEPALA MADRASAH DALAM MEMBANGUN BUDAYA RELIGIUSITAS DI MADRASAH ALIYAH NEGERI 2 KOTA JAMBI - Nur Kamila Hadia R; Atiah Almubarokah; Vindia Putri; Ahmad Ridwan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the leadership role of the principal of State Islamic Senior High School 2 in Jambi City in building and strengthening religious culture in the madrasah. The study used a descriptive qualitative approach with informants consisting of the madrasah principal, Islamic Religious Education teachers, and student representatives who are active in religious activities. Data were collected through observation, interviews, and documentation. The results of the study indicate that the madrasah principal plays a central role through exemplary behavior, direction, supervision, and motivation to teachers and students. The presence of the madrasah principal in the activities of dhuha prayer, tadarus, congregational zuhur prayer, and moral development are real examples that strengthen discipline and participation of the madrasah community. In addition, coordination strategies, scheduling, and utilization of worship facilities effectively support the smooth running of religious programs. These findings confirm that the active, communicative, and supportive leadership of the madrasah principal is a key factor in the formation of a consistent religious culture that is embedded in the daily behavior of students, teachers, and all madrasah members.